EDUCATION, SECURITY AND HEALTH CHALLENGES IN COVID 19 NIGERIA: REFLECTING ON THE ROLE OF ALMAJIRAI - Omolara Victoria Akinyemi Omolara; Adeyemi Kamil HAMZAH (UIN Sunan Gunung Djati Bandung, 2021)
African countries have been severely harmed by terrorism, insurgency, secession, instability, violence and religious crises since the beginning of the 21st century. Countries are on the verge of collapse, wars engulf society, and instability remains a recurring experience since the collapse of colonial rule and subsequent independence from African nations. The increasing incidence of the insecurity crisis in Nigeria is worrying enough to emphasize that the West African regional organizations that have legal responsibility for insecurity management have not been able to adequately address this issue. Nigeria's security challenges seem to be getting worse, threatening the fundamental development and health and education challenges of our nation especially for you almajiri. National security has become a troubling and challenging issue. Therefore, the main purpose of this study is to prove the truth of the existence of a negative correlation between the transmission of covid19, education and other related hazards by the almajiri system. This study uses qualitative research methods with several analytical techniques and several ways of collecting data. This study resulted in recommendations for constitutional reform. Primary and secondary data collection sources are used to provide direction and give credence to the originality of this work and recommendations will be offered for policy makers to consider future steps.